Systematic review of search for meaning in life assessment tools: highlighting the need for a quest for significance scale - Alsaadi, Fahd; Maldonado, Miguel A.; Erfanikia, Mohammad; Molinario, Erica; Moyano, Manuel (Frontiers in Psychology, 2025)
ObjectiveThis systematic review aims to evaluate the adequacy of existing assessment tools in measuring the search for meaning in life and the quest for significance, with a focus on identifying gaps in capturing the quest for significance as a distinct construct.MethodologyFollowing the PRISMA protocol, we conducted a comprehensive search across ProQuest, Web of Science, and Scopus, identifying 23 relevant studies. Methodological quality was assessed using the Downs and Black checklist and the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist. A bibliometric analysis was also performed to explore research trends and collaboration patterns.Key findingsWhile numerous instruments exist, none fully address the quest for significance as a standalone construct. Key limitations include insufficient differentiation between personal and social significance, lack of predictive validity, and limited cultural adaptability.Conclusion and implicationsThe findings underscore the need for a dedicated Quest for Significance Scale to advance psychological research and practice. Future efforts should focus on developing robust, culturally adaptable instruments to better understand the quest for significance across diverse contexts.